DIRĀSAH AL-MUQĀRANAH AL-ADABIYAH FI RIWĀYAH BELĀD BELĀ SAMA' WA RIWĀYAH 'AẒRA JĀKARTA - Maghfiroh, Devi Laila; Masadi, M. Anwar (Annual International Conferences on Language, Literature, and Media; No 1: 3rd AICOLLIM (Annual International Conference on Language, Literature, and Media), 2021)
This research explains the differences and similarities in the forms and representations of stereotypical ideas of women in Yemeni and Indonesian society in the novel “A Country Without a Sky” by Wajdi Al-Ahdal and “The Virgin of Jakarta” by Najib Al-Kilani. It uses comparative literature and Helen Sixus feminism focusing on the dualistic patriarchal opposition.  Data collection techniques used reading and taking notes. The analysis refers to the comparative literary analysis model by François Just, through the phases of object-deepening, subject-study and focus analysis. The results show the similarity of the forms of stereotyped ideas of women that the Yemeni and the Indonesian women are beautiful and contradictory. The stereotypes about Indonesian society are more fluid than the Yemenis. The similarity of the main social representations behind the stereotypical notions of is the ideology that attempts to eradicate religion from human life. The ideology of secularism and communism requires people to separate religion from life. The social and cultural differences between Yemenis and Indonesians are due to the difference in the year of the novel, 1965 and 2008. The distance that separates the distant years will certainly describe a completely different life.